2021
DOI: 10.1088/1361-6528/ac20fc
|View full text |Cite
|
Sign up to set email alerts
|

Electric-field-induced crossover of polarization reversal mechanisms in Al1−x Sc x N ferroelectrics

Abstract: Scandium-doped aluminum nitride, Al1−x Sc x N, represents a new class of displacive ferroelectric materials with high polarization and sharp hysteresis along with high-temperature resilience, facile synthesizability and compatibility with standard CMOS fabrication techniques. The fundamental physics behind the transformation of unswitchable piezoelectric AlN into switchable Al–Sc–N ferroelectrics depends upon important atomic properties such as local structure, dopant distributions and the presence of competin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 71 publications
2
10
0
Order By: Relevance
“…The assumption of this model of a switching process limited by domain wall nucleation occurring independently inside some specific polar regions of the material well agrees with the picture provided by DFT simulations that show that the polarization reversal in Al 1−x Sc x N is initiated at Sc-rich regions. 35 Figure 2a,b demonstrates that cooling down to room temperature after having reached 673 K results in almost exactly the same values of the coercive field. The nonhysteretic E c temperature dependence in Al 1−x Sc x N observed by Gund et al 23 up to 466 K can actually be achieved in a much broader temperature range up to 673 K. Figure 2c and Figure 2d report the temperature dependence of both P sw± and FWHM ± for positive and negative applied electric fields, respectively.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…The assumption of this model of a switching process limited by domain wall nucleation occurring independently inside some specific polar regions of the material well agrees with the picture provided by DFT simulations that show that the polarization reversal in Al 1−x Sc x N is initiated at Sc-rich regions. 35 Figure 2a,b demonstrates that cooling down to room temperature after having reached 673 K results in almost exactly the same values of the coercive field. The nonhysteretic E c temperature dependence in Al 1−x Sc x N observed by Gund et al 23 up to 466 K can actually be achieved in a much broader temperature range up to 673 K. Figure 2c and Figure 2d report the temperature dependence of both P sw± and FWHM ± for positive and negative applied electric fields, respectively.…”
Section: Resultsmentioning
confidence: 65%
“…16 DFT simulations also show that a more inhomogeneous distribution of the Sccontent is expected to be responsible for a reduction of the energy barrier for polarization reversal. 35 On the other hand, cooling down the capacitors, the fitting intercept changes again at 573 K. At temperatures lower than 573 K, the intercept and the energy barrier for ferroelectric switching are larger than those above this temperature. Defects are known to control the thermodynamic stability of local polarization states and the kinetic path for polarization switching.…”
Section: Temperature-dependent Electricalmentioning
confidence: 95%
“…Moreover, due to the strong chemical bonding at the ScAlN/GaN interface and the relatively small dielectric constant of ScAlN (thus stronger depolarization field), a thin non‐switchable paraelectric ScAlN layer or pinned domains could exist, which significantly compensates the overall switchable polarization and weakens the ferroelectric field effect, leading to excessively attenuated depletion widths. [ 41,57 ] The latter is believed to be the main reason for the tailored depletion region in this work. Besides, vacancies could also accumulate at the interface and screen the polarization charges.…”
Section: Resultsmentioning
confidence: 86%
“…[ 5 ] In our case, the complete reorientation of the wurtzite structure requires a holistic displacement of metal or nitrogen atoms, which may evoke some vacancy migration events. [ 57 ] By varying the diameter of the electrodes from 3 to 50 µm, the I – V hysteresis loop is found to be independent of junction area (Figure S8, Supporting Information), and no electroforming or current compliance is required to stabilize the switchable resistance, thereby excluding the formation of conductive filaments. On the other hand, the ON current in this work appears symmetric and is always larger than the OFF current under both biasing conditions, which is different from the typical diode‐like hysteresis loop during electronic conductor–insulator transition.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 Moreover, microscopic models of FEM, e.g., AlScN-based systems, have recently been achieved by simulations. [20][21][22][23] Additionally, calculations have demonstrated that AlN models with nitrogen vacancy at the interior/subsurface locations showed larger formation energies than AlN models with nitrogen vacancy at the surface location, because the formation of nitrogen vacancy at the surface location involves the breaking of a smaller number of Al-N bonds than that for the formation of nitrogen vacancy at interior or subsurface locations. 24 However, very little is known about the role of distortions (e.g., the effects of structural relaxation on bonding/ formation-energy properties) and vacancies in FE thin films.…”
Section: Introductionmentioning
confidence: 99%